Formulation and Evaluation of Gas Powered Systems of Cefixime Tablets for Controlled Release - RAGHAVENDRA RAO N. G; PENTEWAR RAM; S. S. BUSSETTI (International Journal of Pharma and Bio Sciences, 2010)
The present invention relates to a pharmaceutical composition providing a combination of spatial and temporal control in the form of tablets for effective therapeutic results. Cefixime is third generation cephalosporin antibiotic. Cefixime is slowly and incompletely absorbed from the GIT, and poor bioavailability 40 - 50%. The gas powered tablets of Cefixime were prepared by direct compression method to increase the gastric retention time using different concentrations of hydrophilic polymers. The powder blend was subjected for pre-compressional parameters. The prepared tablets were subjected to post compressional analysis for the parameters such as hardness, friability, weight variation, thickness, diameter, drug content, lag time subsequently buoyancy time, and in-vitro dissolution studies. Drug compatibility with excipients was checked by DSC and FTIR studies. In all the formulations, hardness test indicated good mechanical strength, friability is less than 1%, indicated that tablets had a good mechanical resistance. The results were revealed that as concentration of sodium bicarbonate increases from 50 - 80 mg/tab there is decrease in drug release but lag time decreases as increase in concentration of sodium bicarbonate and duration of floating has been increased with increase in concentration of sodium bicarbonate. DSC and FT-IR studies revealed that, there was no incompatibility of the drug with the excipients used. The stability study conducted as per the ICH guidelines and the formulations were found to be stable. From this study, it can be concluded that, the formulation retained for longer periods of time in the stomach (spatial control) and provides controlled release of the drug. Hence, improve the therapeutic effect of the drug by increasing its bioavailability.